E-082 Endovascular preoperative embolization for temporomandibular joint replacement surgery. (22nd July 2019) - Santillan, A; Sur, M; Schwarz, J; Brown, K; Rogol, E; Behrman, D; Patsalides, A
Abstract : Background and purpose: This retrospective study evaluates the safety and effectiveness of preoperative endovascular embolization in patients who underwent temporomandibular joint (TMJ) replacement surgery. Material and methods: We included all patients treated with preoperative embolization of the internal maxillary artery (IMAX) between June 2016 and January 2019. All patients were treated by the same surgeon using standard surgical approaches and procedures. Periprocedural adverse events, blood loss during surgery and clinical follow-up are reported. Results: Fourteen patients (12 females, mean age 32.5) were treated with 19 embolizations of the internal maxillary artery (bilateral embolizations in 7 patients) prior to TMJ replacement surgery with prosthetic joints (TMJ Concepts prostheses). Seven patients presented with TMJ ankylosis/degenerative joint disease/post-trauma deformity, 4 patients with Idiopathic Condylar Resorption and resultant mandibular displacement/hypoplasia, 2 patients with rheumatoid arthritis-associated condylar degeneration and resultant loss of mandibular position, and 1 patient being re-reconstructed following management of a prosthetic joint infection. Seven patients underwent bilateral prosthetic joint replacement. Four patients underwent additional facial skeletal surgery as part of their treatment. The median blood volume loss during TMJ surgery was approximately 370 cc per patient and 246 cc per TMJ replacement surgery (range 100 cc to 800 cc). Joint space-specific blood loss was not recorded but, as per the surgical team, was significantly decreased when compared to non-embolized patients. There were no intra-procedural complications. The mean clinical follow-up was 7.1 months (range 1–24 months). The modified Rankin scale (mRS) was 0 before the procedure and at last clinical follow-up in all patients. After TMJ surgery, 3 patients reported paresthesia of the trigeminal nerve likely related to the residual condyle resection and 3 patients had mild facial nerve weakness (Temporal and/or Marginal Mandibular branch) related to the surgical exposures. Conclusion: Endovascular preoperative embolization of the internal maxillary artery (IMAX) is feasible and safe and likely effective in reducing blood volume loss in complex TMJ replacement surgery. Disclosures: A. Santillan: None. M. Sur: None. J. Schwarz: None. K. Brown: None. E. Rogol: None. D. Behrman: None. A. Patsalides: None.